1996
DOI: 10.1063/1.361820
|View full text |Cite
|
Sign up to set email alerts
|

Formation of supersaturated solid solutions in the immiscible Ni–Ag system by mechanical alloying

Abstract: The mechanical alloying process in the immiscible Ni-Ag system with a positive heat of mixing was investigated by x-ray diffraction and differential scanning calorimetry. High energy ball milling of mixed elemental powders, with nominal composition Ni x Ag 100Ϫx (x ϭ 95, 90, 70, 50, and 30͒, results in the formation of mixtures of supersaturated, nanocrystalline Ni-rich and Ag-rich solid solutions. The solubilities and final grain sizes of these phases depend on the nominal composition of the powder. The maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(44 citation statements)
references
References 34 publications
3
38
3
Order By: Relevance
“…[4] In contrast, in systems with high positive heat of mixing, such as Ni-Ag or Ag-Fe, only extended solubilities could be obtained. [7,12,40] Besides thermodynamic considerations, it is proposed that large differences in strength of the individual phases of the composites can lead to strong strain localization, thereby, impeding to achieve full supersaturation during deformation. [41] Since dislocations play a key role in the kinetic roughening model and the dislocation shuffling process, which are proposed to be mechanisms for deformation-induced mixing, the crystal structures of the present phases might additionally influence the amount of mixing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] In contrast, in systems with high positive heat of mixing, such as Ni-Ag or Ag-Fe, only extended solubilities could be obtained. [7,12,40] Besides thermodynamic considerations, it is proposed that large differences in strength of the individual phases of the composites can lead to strong strain localization, thereby, impeding to achieve full supersaturation during deformation. [41] Since dislocations play a key role in the kinetic roughening model and the dislocation shuffling process, which are proposed to be mechanisms for deformation-induced mixing, the crystal structures of the present phases might additionally influence the amount of mixing.…”
Section: Introductionmentioning
confidence: 99%
“…Extended solubilities or complete supersaturation was achieved in many material systems, such as Cu-Cr, [1] Cu-W, [2] Cu-Co, [3] Cu-Ag, [4][5][6] Ni-Ag, [7] Cu-Fe, [8][9][10][11] or Ag-Fe. [12] A review on mechanical alloying can be found in ref.…”
Section: Introductionmentioning
confidence: 99%
“…Since the solidification cooling rate is inversely proportional to the space between the secondary arms of the dendrites, from It is observed that the addition of Ag favors an increase in the ratio γ-γ′/β due to the reduction in the number and volume of the interdendritic phase (Figure 3(b)). Because of the low solubility of Ag in Ni [56], it is possible to observe the presence of Ag-rich phases. According to Zhou and Guo [57,58], the presence of Ag at grain boundaries begins during the solidification process since this element segregates at the solid-liquid interface, and at the same time, the Ag solubility decreases causing their precipitation into the grains.…”
Section: Microstructural Analysismentioning
confidence: 99%
“…Several efforts to produce such a solid solution by creating metastable states under extreme conditions, such as liquid quenching, did not lead to a reproducible fabrication procedure. The formation of the solid solution was only reported on thin films using laser ablation deposition [ 10,11 ], co-evaporation method [ 12], and recently mechanical alloying [13]. Taking advantage of the high surface-to-bulk energy ratio, which is characteristic of nanocrystals, we were able to prepare samples [7] containing significant amounts of AgNi alloy phase with a wide range of compositions using a co-evaporation of Ag and Ni.…”
Section: Agni Nanocomposite Powdersmentioning
confidence: 99%